Long-Term Mean Circulation of the Baltic Sea as Represented by Various Ocean Circulation Models - Placke, Manja; Meier, H. E. Markus; Gräwe, Ulf; Neumann, Thomas; Frauen, Claudia; Liu, Ye (Frontiers in Marine Science, 2018)
The skill of the state-of-the-art ocean circulation models GETM (General Estuarine Transport Model), RCO (Rossby Centre Ocean model), and MOM (Modular Ocean Model) to represent hydrographic conditions and the mean circulation of the Baltic Sea is investigated. The study contains an assessment of vertical temperature and salinity profiles as well as various statistical time series analyses of temperature and salinity for different depths at specific representative monitoring stations. Simulation results for 1970-1999 are compared to observations from the Baltic Environmental Database (BED). Further, we analyze current velocities and volume transports both in the horizontal plane and through three transects in the Baltic Sea. Simulated current velocities are validated against ten years of Acoustic Doppler Current Profiler (ADCP) measurements in the Arkona Basin and five years of mooring observations in the Gotland Basin. Furthermore, the atmospheric forcing datasets, which drive the models, are evaluated using wind measurements from 28 automatic stations along the Swedish coast. We found that the seasonal cycle, variability, and vertical profiles of temperature and salinity are simulated close to observations by RCO with an assimilation setup. All models reproduce temperature well near the sea surface. Salinity simulations are of lower quality from GETM in the northern Baltic Sea and from MOM at various stations. Simulated current velocities lie mainly within the standard deviation of the measurements at the two monitoring stations. However, sea surface currents and transports in the ocean interior are significantly larger in GETM than in the other models. Although simulated hydrographic profiles agree predominantly well with observations, the mean circulation differs considerably between the models highlighting the need for additional long-term current measurements to assess the mean circulation in ocean models. With the help of reanalysis data ocean state estimates of regions and time periods without observations are improved. However, due to the lack of current measurements only the baroclinic velocities of the reanalyses are reliable. A substantial part of the differences in barotropic velocities between the three ocean models and reanalysis data is explained by differences in wind velocities of the atmospheric forcing datasets.